Radiation control of microstrip patch antenna by using electromagnetic band gap - Abdulhammed, Muhannad Kaml; Mohamad Isa, Mohd Sa'ari; Zakaria, Zahriladha; Mohd Ibrahim, Imran; Mohsen, Mowafak Khadom; Attiah, Mothana Lafta; Dinar, Ahmed Musa (Elsevier GmbH, 2019)
In this paper, two compact electromagnetic band gap (EBG) antennas are proposed by combining a rectangular antenna with a mushroom-like EBG structure and with a novel triple side-slotted EBG (TSSEBG). Both prototype antennas can scan the main beam in the elevation (E) (-20' < u < 20'), (-17' < u < 17') and horizontal (H) (-18' < h < 18'), (-15' < h < 15') planes, respectively. The main beam scanning was conducted by using band-stop and band-pass properties. The band-stop property was achieved by connecting the vias to the ground plane of the antenna, whereas the band-pass property was realized by disconnecting the same vias, thereby yielding the beam steering into the pass-band sector. Unlike usual beam steering, this technique does not suffer from gain degradation, and the gain of the main lobe is approximately stable for the steering angles. The antenna performance was enhanced due to suppress surface waves. Moreover, the number of vias was reduced significantly in the proposed TSSEBG instead of the mushroom-like EBG. The compact EBG and TSSEBG antennas have directivity (10 and 10.5) dBi, gain (9.86 and 10.16) dB, and efficiencies of 96.5% and 93%, respectively, with the operating frequency at 6 GHz